Innovation in the University Classroom Through Augmented Reality. Analysis From the Perspective of the Spanish and Latin American Students - Cabero-Almenara, Julio (2021)
Objective. This article analyzes the experiences of university innovation with immersive technologies (Augmented Reality, RA) of various degree programs at the Pablo de Olavide University of Seville (Spain) and the Catholic University of Santiago de Guayaquil (Ecuador) corresponding to the academic year 2018-2019. Method. Through a mixed methodology of data analysis (quantitative and qualitative) and the design of an ad hoc questionnaire of own elaboration, the perceptions of 202 students were analyzed in relation to the advantages and disadvantages of the RA and the Augmented Reality apps used in the Emerging Technologies seminars in educational contexts, taught in both universities. Results. The results show that the most valued mobile applications were QuiverVisión and HP Reveal because of their interactivity, wearable environment, and educational projection in formative contexts, especially at early ages. Conclusions. Students perceive the development of cognitive skills and the development of competencies as the main advantages of RA. Likewise, as main disadvantages, the need for university teacher training for classroom implementation and the possible adverse effects of the digital divide.